214k views
3 votes
Which expressions are completely factored? Select each correct answer. 18y^3−6y=3y(6y^2−2) 32y^10−24=8(4y^10−3) 20y^7+10y^2=5y(4y^6+2y) 16y^5+12y^3=4y^3(4y^2+3)

User Skeep
by
5.7k points

1 Answer

5 votes

Answer:

The expressions that completely factored are:


32y^(10)-24 = 8(
y^(10)-3) ⇒ 2nd


16y^(5)+12y^(3)=4y^(3)(4y^(2)+3)4th

Explanation:

Complete factorization means the terms in the bracket has no common factor

∵ The expression is 18y³ - 6y

- Find the greatest common factor of the numbers and the variable

∵ The greatest common factor of 18 and 6 is 6

∵ The greatest common factor of y³ and y is y

∴ The greatest common factor is 6y

- Divide each term by 6y to find the terms in the bracket

∴ 18y³ - 6y = 6y(3y² - 1) ⇒ not the same with the answer

∵ The expression is
32y^(10)-24

∵ The greatest common factor of 32 and 24 is 8

∴ The greatest common factor is 8

- Divide each term by 8 to find the terms in the bracket


32y^(10)-24 = 8(
y^(10)-3) ⇒ the same with the answer

The expression
32y^(10)-24 = 8(
y^(10)-3) is completely factored

∵ The expression is
20y^(7)+10y^(2)

∵ The greatest common factor of 20 and 10 is 10

∵ The greatest common factor of
y^(7) and y² is y²

∴ The greatest common factor is 10y²

- Divide each term by 10y² to find the terms in the bracket


20y^(7)+10y^(2)=10y^(2)(2y^(5)+1) ⇒ not the same with the answer

∵ The expression is
16y^(5)+12y^(3)

∵ The greatest common factor of 16 and 12 is 4

∵ The greatest common factor of
y^(5) and y³ is y³

∴ The greatest common factor is 4y³

- Divide each term by 4y³ to find the terms in the bracket


16y^(5)+12y^(3)=4y^(3)(4y^(2)+3) ⇒ the same with the answer

The expression
16y^(5)+12y^(3)=4y^(3)(4y^(2)+3) is completely factored

The expressions that completely factored are:


32y^(10)-24 = 8(
y^(10)-3)


16y^(5)+12y^(3)=4y^(3)(4y^(2)+3)

User Daotoad
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.